Pyramidal multiple‐theory (multi‐type, multi‐method and multi‐layer) for facial fat grafting. (27th December 2022) - Hu, Hao; Shi, Yingshen; Qian, Yuxin; Yu, Xiaoyan; Liu, Antang; Li, Facheng; Jiang, Hua; Wang, Hui
Abstract: Background: Age‐related changes to the face pertinent anatomy and important aspects of autologous fat grafting have been widely applied in facial rejuvenation. Various types of autologous fat products (Macrofat, Microfat, SEFF, nanofat, and SVF‐gel) with different properties and applicabilities have been introduced and available for surgeons. Methods: Key differences between common techniques for fat processing and infiltration. Develop a plan for patients based on site‐specific facial anatomical zones, we suggested a pyramidal multiple‐theory (multi‐type, multi‐method and multi‐layer) for facial fat grafting. Based on the complicated mechanism of the face decrepitude in different layers of facial soft tissue, autologous fat products with various particle sizes and components into different layers. Results: Fifty‐eight patients underwent this facial fat grafting strategy from June 2020 to Jan 2022. All achieved cosmetic improvements, with higher patients' satisfaction, and minor complications. Our facial fat grafting strategy takes advantage of different fat products and is able to address the physiological tissue changes during aging, more properly and targetedly, than the traditional facial fat grafting. Conclusions: Fat grafting to the face aids in volume restoration and rejuvenation, thereby addressing soft‐tissue atrophy associated with the aging face, acquired conditions, or congenital malformations. The technique described as "lipo‐tumescence" has been successfully used in the breast and other regions of the body that have radiation damage and is discussed in this article specifically for the face and neck.